2020
DOI: 10.1111/codi.15292
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extended right hemicolectomy, left hemicolectomy and segmental colectomy for splenic flexure colon cancer: a systematic review and meta‐analysis

Abstract: Aim The aim of this work was to compare the outcomes of extended right hemicolectomy (ERH), left hemicolectomy (LH) and segmental colectomy (SC) for the surgical management of splenic flexure tumours. Method In compliance with PRISMA statement standards, a systematic review was performed to identify all studies comparing outcomes of ERH, LH and SC for the surgical management of splenic flexure tumours. Primary outcomes included anastomotic leakage and all postoperative complications. The secondary outcomes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
3
19
0
1
Order By: Relevance
“…We read with great interest the systematic review and meta‐analysis by Hajibandeh and colleagues [1], and we congratulate them on their comprehensive analysis. The authors concluded that the outcomes of extended right hemicolectomy (ERH), left hemicolectomy (LH), and segmental colectomy (SC) were similar with respect to the surgical management of splenic flexure colon cancer (SFC).…”
mentioning
confidence: 99%
“…We read with great interest the systematic review and meta‐analysis by Hajibandeh and colleagues [1], and we congratulate them on their comprehensive analysis. The authors concluded that the outcomes of extended right hemicolectomy (ERH), left hemicolectomy (LH), and segmental colectomy (SC) were similar with respect to the surgical management of splenic flexure colon cancer (SFC).…”
mentioning
confidence: 99%
“…Besides, SCR for transverse colon cancer was associated with less ileus but higher anastomotic leak rates and lower lymph node yields, and similar hospital stay [ 69 ]. For splenic flexure cancer, there was no difference in morbidity and mortality, the rate of lymph node yields and survival rate between SCR and LCR groups [ 68 ], and the operation time and hospital stay were shorter [ 71 ]. However, there was still a lack of reports on SCR for hepatic flexure cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Closing the mesenteric defect helps prevent the development of internal hernia. This is a rather rare complication, with a prevalence of 0.5% [3,4]. Despite being rare, this event should be kept in mind by the colorectal surgeon because it can potentially lead to bowel ischaemia or necrosis if herniated loops are trapped below the mesenteric defect, exposing the patient to high morbidity and mortality rates [5].…”
Section: Dear Sirmentioning
confidence: 99%